2009
DOI: 10.1371/journal.pone.0005478
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Discovery in Subclinical Mycobacterial Infections of Cattle

Abstract: BackgroundBovine tuberculosis is a highly prevalent infectious disease of cattle worldwide; however, infection in the United States is limited to 0.01% of dairy herds. Thus detection of bovine TB is confounded by high background infection with M. avium subsp. paratuberculosis. The present study addresses variations in the circulating peptidome based on the pathogenesis of two biologically similar mycobacterial diseases of cattle.Methodology/Principal FindingsWe hypothesized that serum proteomes of animals in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 33 publications
(34 reference statements)
3
87
3
Order By: Relevance
“…paratuberculosis infection. A detailed description of the sample processing and analysis using iTRAQ was described by Seth et al (13). Host-specific peptides and relative abundance (Ͼ95% confidence interval [CI]) were identified using the ProteinPilot software 2.0 and 2.01 (Applied Biosystems, Inc., Foster City, CA) and the nr_bos_CTM_20070802 FASTA database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…paratuberculosis infection. A detailed description of the sample processing and analysis using iTRAQ was described by Seth et al (13). Host-specific peptides and relative abundance (Ͼ95% confidence interval [CI]) were identified using the ProteinPilot software 2.0 and 2.01 (Applied Biosystems, Inc., Foster City, CA) and the nr_bos_CTM_20070802 FASTA database.…”
Section: Methodsmentioning
confidence: 99%
“…In order to minimize cross-reactivity, we identified 32 host and 16 pathogen circulating peptides that are unique to M. bovis infection and followed up over a 5-month period using a highly sensitive proteomics approach (13). During infection, Mycobacterium-specific proteins, peptides, DNA, and lipids are released into the circulation (14,15) and are likely to provide unprecedented specificity to identify M. bovis infection.…”
mentioning
confidence: 99%
“…The prevalence is unknown in many parts of the world, but in the United States it has been recently estimated to affect as high as 68% of dairy herds. 17 Economic losses result directly from reduced milk yield, premature culling, and reduced slaughter value and indirectly as shedding adults serve as a source of infection for susceptible herd mates and young calves. 12 A considerable amount of research using a variety of experimental model systems has been devoted to this disease in recent years, yet the pathogenesis of intestinal Map infection remains incompletely understood.…”
mentioning
confidence: 99%
“…In addition, SECTM1 has been shown to be a cognate of CD7, a protein found on T-cells, natural killer cells and pre-B cells and, while the function of SECTM1 is not well established [27], the SECTM1 cognate has been reported to stimulate the upregulation of CD25, CD54 and CD69 on human natural killer cells in vitro in TB infection. Furthermore, serum levels of AMBP have also been observed to be elevated levels in cattle with sub-clinical M. bovis infections [25]. Reduced levels of PTGDS have been reported in cerebrospinal fluid samples from patients with bacterial meningitis [28]; however, to our knowledge there has been no previous correlation between PTGDS and TB.…”
Section: Discussionmentioning
confidence: 91%
“…A number of these have been previously observed to be associated with TB infection. For example, two related studies showed that RBP4 was a marker for TB infection, with elevated levels of RBP4 being found in the serum of cattle infected with Mycobacterium bovis [25] and with differential expression of RBP4 being observed in human whole blood supernatant [26]. In addition, SECTM1 has been shown to be a cognate of CD7, a protein found on T-cells, natural killer cells and pre-B cells and, while the function of SECTM1 is not well established [27], the SECTM1 cognate has been reported to stimulate the upregulation of CD25, CD54 and CD69 on human natural killer cells in vitro in TB infection.…”
Section: Discussionmentioning
confidence: 99%